USTRÓJ I SPOŁECZEŃSTWO GALIJSKIE W ŚWIETLE ‘DE BELLO GALLICO’ CEZARA - Korporowicz, Łukasz Jan (Zeszyty Prawnicze, 2016)
POLITICAL AND SOCIAL ORGANISATION OF GAULS IN THE LIGHT OF CAESAR’S ‘DE BELLO GALLICO’ Summary Caesar’s De bello Gallico is currently the only source of our knowledge about ancient Celtic law. Careful reading of Caesar’s work let modern scholars to describe some general principles of Celtic legal order. It is, however, important to remember that De bello Gallico was not a legal treaty and was not written by a lawyer. Additionally it can be assumed that Caesar used his work as a tool of political propaganda. All those circumstances encumber a precise analysis of Gallic law. The most specific information about Gallic law described in De bello Gallico concerns political organization of Gauls and their society. Caesar wrote about general assembly of all Gallic tribes, general assembly of the druids, some local assemblies and tribal officials. He wrote also quite extensively about private law e.g. about segregation of the society (druids, aristocracy, commoners, slaves), clients, family relations.